Teaching Critical Thinking - กว้างสวาสดิ์, ธูปทอง (Ratchaphruek Journal, 2018)
Critical thinking is an essential skill for society nowadays. Thus, teaching critical thinking skills is necessary for our students. Critical thinking is not only thinking clearly or rationally but also thinking independently. It is related to the discipline of analysis, and seeing the relationship between ideas. Teaching critical thinking requires curiosity and open minds, along with a few strategies. Every teacher is trying to find different ways to integrate it into classrooms. Therefore, this article discusses beneficial techniques for teaching critical thinking skills in order that the teachers can adapt the techniques to their lessons.